The impact of sleep disturbances on care home residents with dementia: the SIESTA qualitative study. (July 2020) - Webster, Lucy; Powell, Kingsley; Costafreda, Sergi G.; Livingston, Gill
ABSTRACT: Objectives: Nearly 40% of care home residents who are living with dementia also have symptoms of disturbed sleep. However, the impact of these disturbances is relatively unknown and is needed to indicate whether interventions are warranted; therefore, we aimed to investigate the impact. Design: One-to-one semi-structured interviews. Settings: Four UK care homes. Participants: We interviewed 18 nurses and care assistants about residents with sleep disturbances. Measurements: We used a topic guide to explore staff experience of sleep disturbance in residents with dementia. The interviews were audio recorded and transcribed and then analyzed thematically by two researchers independently. Results: Staff described that sleep disturbances in most, but not all, residents impacted negatively on the resident, other residents, staff, and relatives. Residents became more irritable or agitated if they had slept badly. They slept in the daytime after a bad night, which then increased their chances of being awake the following night. For some, being sleepy in the day led to falls, missing medication, drinks, and meals. Staff perceived hypnotics as having low efficacy, but increasing the risk of falls and drowsiness. Other residents were disturbed by noise, and staff described stress when several residents had sleep disturbance. Some of the strategies reported by staff to deal with sleep disturbances such as feeding or providing caffeinated tea at night might be counterproductive. Conclusions: Sleep disturbances in care home residents living with dementia negatively affect their physical and psychological well-being. These disturbances also disturb other residents and increase stress in staff.